Metodologi Khusus Penafsiran Al-Quran dalam Kitab Tafsir Al-Maraghi - Farhan Ahsan Anshari; Hilmi Rahman (Jurnal Iman dan Spiritualitas, 2021)
Tafsir as an explanation for the holy book of the Al-Qur'an is one of the studies that never goes out of the way. The reason is that as an important branch of Islamic scholarship, it is one of the things that continues to be done considering that Muslims are obliged to understand the book of instructions. Overall the method of interpretation is divided into four in general, namely tahlili, ijmali, muqaran and maudhu'i. Among the tafsir books that use the tahili method in modern times is the al-Maraghi interpretation written by a mufassir named Ahmad Mustafa al-Maraghi. He has been devoting his skills in interpreting the Qur'an for 10 years with a distinction in it. Al-Maraghi in interpreting Alquan has a special method, namely classifying verses, explaining globally, explaining groups of verses in detail and presenting a history in explaining them. Then the interpretation of al-Maraghi is also away from the terms of science or science because the style of interpretation chosen is al-adab al-ijtima'i.